Improving Drama Script Writing Skills Through Method of Learning Scientific Grade VIII Junior High School Negeri 1 Selong Years Lessons 2013/2014 - Mohzana Mohzana (VELES Voices of English Language Education Society, 2017)
Writing skills is the ability to use language to communicate wearing good writing language in accordance with linguistic rules. Skills would be achieved if a lot of practice. Therefore, to attain skills that students should be given a lot of the writing exercise. Based on observations made by researchers in the SMP Negeri 1 Selong, apparently the result of the student's writing is still low. The cause, underprivileged students in pouring the idea (idea), lack of students to practice writing. As such, the drama script writing skills in students of class VIII SMP Negeri 1 Selong needs to be improved. Improve the writing skills of students through scientific learning methods. This type of research this is a class action Research (PTK) that done in two cycles, the subject of this research is the class VIII SMP Negeri 1 Selong School Year 2013/2014. In this study, researchers used the technique of observation and test techniques for collecting data, and then to analyze the data already gathered researchers using the technique of descriptive qualitative and descriptive techniques quantitative with the formula Mi-Sdi. Based on the results of the analysis it can be concluded that Scientific learning methods can improve the ability of writing a screenplay on the learning process of students. Increase in the ability of students in writing the script of the play seen from the classical mastery in percentage of the cycle I of 24% experienced an increase in cycle II with mastery in classical 89%.